Pathogenic viruses associated with bats of Malaysia - Balinu, C.P; Daim, S; Chua, T.H (Malaysian Society of Parasitology and Tropical Medicine, 2024)
Numerous human diseases, including those caused by viruses like Nipah virus and SARS-CoV, can be traced back to bats as their origin. Malaysia, notably Sabah and Sarawak in Borneo Island, is home to a rich diversity of bats that serve as hosts for various viruses. This comprehensive review represents the inaugural exploration of viruses found in Malaysian bats, as documented in scientific journals. It also encompasses documented instances of bat virus-related disease outbreaks in Malaysia up to the present day, along with an analysis of the risk factors associated with virus spillover events. Furthermore, this review offers insights into prospective research areas of significance and suggests potential mitigation strategies.